GPS-free synchronized pseudo-random number generators for internet-of-things - Rahman, Mustafizur; Chakrabartty, Shantanu (Frontiers in Computer Science, 2023)
Securing wireless communications in internet-of-things (IoT) requires both generation and synchronization of random numbers in real-time. However, resource constraints on an IoT device limit the use of computationally intensive random number generators and the use of global positioning systems (GPS) for synchronization. In this paper, we propose a synchronized pseudo-random number generator (SPRNG) that uses a combination of a fast, low-complexity linear-feedback-shift-register (LFSR) based PRNG and a slow but secure, synchronized seed generator based on self-powered timers. The synchronized self-powered timers (SSPTs) use quantum-mechanical tunneling of electrons to operate without any external power and are practically secure against tampering, snooping, and side-channel attacks (both power and electromagnetic). In this work, we explore protocols to periodically and securely generate random bits using the self-powered timers for seeding the LFSR. The time-varying random seeds extend and break the LFSR periodic cycles, thus making it difficult for an attacker to predict the random output or the random seed. Using the National Institute of Standards and Technology (NIST) test suite we verify the randomness of the measured seeds using an ensemble of self-powered timers fabricated in a standard CMOS process and the random bit sequences generated by a software-seeded LFSR. In this modality, the proposed SPRNG could be used as a trusted platform module (TPM) on IoTs and used for verifying and authenticating secure transactions (e.g. software upgrades).